Trust and antitrust in Asian business alliences : - Kidd, John B. (Palgrave McMillan, 2004)
This book explores cutting-edge models and practices that support cultural alliances over boundaries. It examines trends in Asia's modification of its economic and fiscal environment, strategies undertaken by multinational companies and governments in Asia in coping with divergent cultures, organizational restructuring to support alliance formation and maintenance and post-crisis strategies. The book illustrates the range of governance structures that are seen to be better (or worse) at supporting alliances and it offers an approach to ameliorating difficulties.